RECONSTRUCTING STRATEGIC MANAGEMENT IN ISLAMIC EDUCATION THROUGH INTERNAL AND EXTERNAL ENVIRONMENTAL ANALYSIS IN THE GLOBAL ERA: A STUDY OF KHAIRU UMMAH NUSRA INTEGRATED ISLAMIC EDUCATIONAL INSTITUTION - Nana Fitrianaa; Lalu Muh. Sulhan Zihadib; Mustamin Hafific; Titiek Rohanah Hidayatid; Erma Fatmawatie (Politea : Jurnal Politik Islam, 2026)
This study aims to reconstruct strategic management in Islamic education through the analysis of internal and external environments in the global era. A qualitative approach with a case study design was employed at Khairu Ummah Nusra Integrated Islamic Educational Institution. Data were collected through in-depth interviews, observation, and documentation involving institutional leaders, teachers, staff, and parents. The data were analyzed using the interactive model of Miles and Huberman and supported by SWOT analysis. The findings reveal that the internal environment shows strengths in human resource commitment and Islamic value-based organizational culture, while weaknesses are found in management systems and technological integration. The external environment provides opportunities through the increasing public demand for Islamic education but presents challenges in terms of institutional competition and rapid technological development. The study also finds that strategic management practices are still partially intuitive and not fully based on systematic environmental analysis. This study concludes that reconstructing strategic management through a comprehensive analysis of internal and external factors is essential to enhance institutional competitiveness in the global era. The integration of Islamic values with modern strategic approaches becomes a key factor in strengthening the sustainability and adaptability of Islamic educational institutions.